THE STUDY OF LIFE QUALITY IN INTERVENTIONAL AND CONSERVATIVE TREATMENTS OF THE PATIENTS WITH STABLE ANGINA AT DELAYED OBSERVATIONS - D. V. Dedov; V. P. Mazaev; S. V. Ryazanova; I. A. Elgardt; A. N. Maslov; I. Yu. Evtyukhin; A. N. Kovalchuk (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To study the life quality parameters in interventional and conservative treatment strategies in patients with stable angina at delayed follow-up periods.Material and methods. Totally 146 patients included with stable angina: main group – 102, comparison group – 44 patients. To the first the stenting or angioplastics of coronary arteries provided, to the second – just drug therapy. Mean follow-up period was 3,6±1,3 years. Life quality parameters were measured in patients.Results. It is shown that in men and women of the main group the physical functionality parameter was higher than in comparison group – by 23,1% and 18,2%, resp. (both with p<0,05). In men of the main group parameters of physical health and pain intensiveness were higher than in women (by 24,6% and 21,4%; both with p<0,01). Positive correlation was found between general health parameters and pain intensiveness, survival function and self-assessment of mental health.Conclusion. It was shown that instable angina patients after interventional treatment tolerability of the physical exertion was higher than in patients received only drug therapy. It was shown that independently from gender and treatment strategy there is interconnection between physical condition and survival function.